Diclofenac degradation based on shape-controlled cuprous oxide nanoparticles prepared by using ionic liquid - Huang, Jialei (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Persulfate oxidation technology is widely used in wastewater treatment, but there are still many disadvantages, such as high energy consumption, side reaction and narrow pH applicability. Copper oxides can activate persulfate steadily with higher efficiency. In this paper, a novel preparation method of shape-controlled cuprous oxide (Cu2O) nanoparticles featured with high catalytic performance was explored. It was found that adding ionic liquid 1-butyl-3-methylimidazolium bromide ([BMIM]Br) during preparation of Cu2O can improve the degradation rate of diclofenac (DCF). Cu2O nanoparticles possess good stability in consecutive cycling tests, which was confirmed by X-ray photoelectron spectroscopy. The possible mechanism of Cu2O activating persulfate at different initial pH conditions was discussed based on electron paramagnetic resonance spin-trapping experiment. It was found that DCF was efficiently degraded in the Cu2O/peroxydisulfate (PDS) system within a broad pH range from 5 to 11. It proved via a quenching experiment that the activation process of PDS mainly occurs on the surface layer of Cu2O nanoparticles. As a result, shape-controlled Cu2O nanoparticles prepared by ionic liquid are expected to be used for in situ chemical oxidation, which is an effective oxidation processes to degrade DCF remaining in surface water and ground water